Chlamydia trachomatis Polymorphic Membrane Proteins (Pmps) Form Functional Homomeric and Heteromeric Oligomers - Favaroni, Alison; Hegemann, Johannes H. (Frontiers in Microbiology, 2021)
Chlamydiae are Gram-negative, obligate intracellular bacteria, which infect animals and humans. Adhesion to host cells, the first step in the infection process, is mediated by polymorphic membrane proteins (Pmps). Pmps constitute the largest chlamydial protein family, with 9 members (subdivided into six subtypes) in C. trachomatis and 21 in C. pneumoniae, and are characterized by the presence of multiple copies of GGA(I,L,V) and FxxN motifs. Motif-rich fragments of all nine C. trachomatis Pmps act as adhesins and are essential for infection. As autotransporters, most Pmp proteins are secreted through their β-barrel domain and localize on the surface of the chlamydial cell, where most of them are proteolytically processed. Classical autotransporters are monomeric proteins, which can function as toxins, proteases, lipases and monoadhesive adhesins. Here we show that selected recombinant C. trachomatis Pmp fragments form functional adhesion-competent multimers. They assemble into homomeric and heteromeric filaments, as revealed by non-denaturing gel electrophoresis, size-exclusion chromatography and electron microscopy. Heteromeric filaments reach 2 µm in length, significantly longer than homomeric structures. Filament formation was independent of the number of motifs present in the fragment(s) concerned and their relative affinity for host cells. Our functional studies demonstrated that only adhesion-competent oligomers were able to block a subsequent infection. Pre-loading of infectious chlamydial cells with adhesion-competent Pmp oligomers maintained the subsequent infection, while adhesion-incompetent structures reduced infectivity, presumably by blocking the function of endogenous Pmps. The very large number of possible heteromeric and homomeric Pmp complexes represents a novel mechanism to ensure stable adhesion and possibly host cell immune escape.